RESTRUKTURISASI PERJANJIAN SEWA BELI KENDARAAN BERMOTOR PADA PT SUMMIT OTO FINANCE PADANG DI MASA PANDEMI COVID-19 - Yoga Prasetyo, Yunimar , (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
Agreement is a legal relationship that is often carried out by people in Indonesia. On April 13, 2020, the Indonesian government, based on Presidential Decree No. 12 of 2020, declared the Corona Virus (COVID-19) a National Disaster. The spread of COVID-19 that has occurred has caused the national economy to decline so that people are unable to fulfill the achievements in the agreement. The Financial Services Authority (OJK) as an institution that has the authority to regulate financial service activities. One of them is a finance company that stipulates OJK Regulation Number 14/POJK.05/2020 concerning Countercyclical Policies for the Impact of the Spread of Corona Virus Disease 2019 for Non-Bank Financial Services Institutions. The results of the study explain that the lease purchase agreement made by PT. Summit Oto Finance Padang with consumers is an agreement with the signing of a motor vehicle rental agreement by the consumer, indicating that the consumer agrees with all the terms of the agreement provided. Implementation of the restructuring of the lease purchase agreement at PT. Summit Oto Finance Padang has realized 270 (two hundred and seventy) agreements. The restructuring of the lease purchase agreement was carried out by extending the term of the agreement, delaying part of installment payments, and reducing principal arrears. The obstacles faced are the declining ability of consumers, consumers who often do past dues (past due installment payments. Solutions related to these obstacles are by giving warning letters to the 1st to 3rd warning letters, giving subpoenas in the form of reprimands, executing vehicles, and file a simple lawsuit to the District Court.